Impact in doctoral education : product, person and process - Parry, Emma (Research manager); Pilbeam, Colin (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Demonstrating how impact can be created and derived from doctoral programmes, this book focuses on their influence on academic knowledge, policy and practice. Significantly it highlights the crucial impact of these programmes on the individual and the enduring consequences of this. Drawing on their extensive experience and conversations with stakeholders in doctoral education from around the world, and incorporating real case examples, the authors provide practical guidance throughout the book which enables readers to enhance the design of new and existing doctoral programmes for greater impact. Each chapter ends with questions to stimulate reflection on the readers' experience of impact from doctoral education. The concluding chapter outlines a manifesto for enhancing and ensuring impact from doctoral research in the future. With insights into the impact of doctoral programmes on individual researchers, this book will be essential reading for scholars of management education, as well as being a valuable resource for higher education administrators and senior academics around the world tasked with increasing impact from their doctoral programmes"--
Introduction -- Section 1. Product -- Scholarly impact of doctoral research -- Practitioner and policy impact of doctoral research -- Section 2. Person -- Impact on individual skills, employability & career progression -- Impact on the individual -- identity transitions -- Section 3. Process -- Supervision and support -- Programme structure and content -- Conclusions.
Keywords: Management -- Study and teaching (Graduate); Management -- Research; Business education -- Evaluation; BUSINESS & ECONOMICS / Education; BUSINESS & ECONOMICS / Management